ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIKA SISWA SMP KELAS IX PADA MATERI BANGUN RUANG SISI LENGKUNG - Santi Shintia; Gida Kadarisma (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This research is a descriptive study with the aim of knowing and analyzing the results of student work on questions of mathematical communication skills. This study took the subjects from private junior high schools in Cimahi as many as 25 grade IX students. The data collection technique is by means of test questions, consisting of 5 questions in description with each question representing one indicator of mathematical communication. Based on the data analysis, it was found that the mathematical communication skills of grade IX junior high school students on the curved side of the building material were quite good. Of the 5 indicators of mathematical communication, there are 2 indicators that are classified as high, namely the indicator that states the situation becomes a mathematical model and the indicator interprets the mathematical model into ordinary language. Then 1 indicator that is classified as moderate, namely the indicator that states daily events become a mathematical symbol and 2 indicators that are classified as low, namely the indicator of interpreting and compiling mathematical questions and the indicator of compiling arguments and writing down the reasons.